Investigating the nexus between FDI, governance quality and green economic growth in various Asian economies - Quang, Phung Thanh; Thao, Doan Phuong; Thao, Dinh Huong (Edelweiss Applied Science and Technology, 2025)
This study explores the complex and dynamic relationships between foreign direct investment (FDI), governance quality, and green economic growth across selected Asian economies during the 2005-2022 period through a Pooled Mean Group (PMG) estimator in a dynamic panel framework. The empirical evidence depicts that there is the halo pollution theory in high and upper middle-income groups of countries, while the haven pollution theory exists in low and lower middle-income groups of countries. Moreover, labor force participation, governance, and financial openness may accelerate green economic growth in both panels of Asian countries, while any increase in the inflation rate and fossil fuel consumption may lead to a lower speed of green growth in both panels of Asian countries. As policy implications, high or upper-middle-income countries in Asia should try to reduce their dependence on fossil fuels, adopt effective strategies in the field of financial openness, improve green employment, and increase the green skills of the workforce, while low or lower-middle-income countries should strive to make R&D more efficient, improve governance indicators, and implement green investment incentive policies.